Final answer:
The inverse function of f(x) = one-half x minus three-halves is f^-1(x) = -2x + 3/2.
Step-by-step explanation:
The inverse function of f(x) = one-half x minus three-halves is f⁻-1(x) = negative one-half x minus three-halves. In order to find the inverse function, we need to swap the x and y variables and solve for y. Let's do that:
- Replace f(x) with y: y = one-half x minus three-halves
- Swap x and y: x = one-half y minus three-halves
- Solve for y by isolating it:
y = -2x + 3/2
Therefore, the inverse function of f(x) = one-half x minus three-halves is f⁻-1(x) = -2x + 3/2.